Carbon mobilization in response to the 2021 Mw 7.4 Maduo earthquake: Constraints from carbon isotope systematics of subsurface fluids - Liu, Yi; Liu, Wei; Zhou, Xiaocheng; Zhong, Jun; Zhang, Maoliang; Xu, Sheng (Frontiers in Earth Science, 2023)
Active fault zones provide favorable channels for the discharge of carbon-bearing fluids from Earth’s interior. Earthquakes, as a common fault-related dynamic process, can disturb the circulation of subsurface fluids and their interactions with country rocks and sediments on short timescales, which may cause changes in carbon mobilization processes and carbon sources of the discharged fluids. However, quantitative research on earthquake-induced changes in carbon mobilization at deep and shallow levels remains lacking. Here, we present a quantitative study on stable carbon isotopes (δ13C) and radiocarbon values (Δ14C) of dissolved inorganic carbon (DIC) in subsurface fluid samples from the surface rupture zone formed by the Mw 7.4 Maduo earthquake (May 22, 2021) and the East Kunlun fault, NE Tibetan Plateau. Our results show that δ13CDIC values vary from –11.6‰ to 0.1‰, while Δ14CDIC values have a range of –980‰ to –46‰. Using a mass balance model based on δ13CDIC and DIC concentrations, we calculated the proportions of source components involved in DIC, including organic carbon, carbonates, and deeply-sourced carbon dioxide (CO2). On average, waters discharging from the surface rupture zone have higher inputs from organic carbon (28.1%) than those from the East Kunlun fault (18.6%), with the latter showing higher deeply-sourced carbon contributions (45.7% vs. 30.7%). This is consistent with the lower average Δ14CDIC value (–544‰) observed from the East Kunlun fault, suggesting more inputs from carbon source components that are devoid of 14C (i.e., deeply-sourced carbon and carbonates). These findings indicate that seismic events can significantly affect the carbon mobilization processes at variable depths, especially the shallow soil organic carbon in the case of the 2021 Maduo earthquake. The potential effects of earthquake-induced changes in carbon mobilization processes should be taken into account in the modeling of tectonic CO2 degassing and carbon cycle on longer timescales.